Synthesis, structure, ionochromic and cytotoxic properties of new 2-(indolin-2-yl)-1,3-tropolones - Sayapin, Yurii A.; Gusakov, Eugeny A.; Tupaeva, Inna O.; Dubonosov, Alexander D.; Dorogan, Igor V.; Tkachev, Valery V.; Goncharova, Anna S.; Shilov, Gennady V.; Kuznetsova, Natalia S.; Filippova, Svetlana Y.; Krasnikova, Tatyana A.; Boumber, Yanis A.; et al. (Beilstein Journal of Organic Chemistry, 2025)
The acid-catalyzed reaction of benzo[e(g)] derivatives of 2,3,3-trimethylindolenines with o-chloranil leads to new 2-(benzo[e(g)]indolin-2-yl)-5,6,7-trichloro-1,3-tropolones and 2-(benzo[e(g)]indolin-2-yl)-4,5,6,7-tetrachloro-1,3-tropolones. Based on the results of PBE0/6-311+G(d,p) calculations, the structural and energetic characteristics of the tautomeric forms of the obtained 1,3-tropolones were determined. The structure of 2-(3,3-dimethyl-3H-benzo[g]indolin-2-yl)-5,6,7-trichloro-1,3-tropolone was determined by X-ray diffraction analysis. The compounds obtained are capable of switching emission at 420–440 nm and 476–530 nm upon successive exposure to CN− and Hg2+ ions in an acetonitrile solution. 2-(1,1-Dimethyl-1H-benzo[e]indolin-2-yl)-5,6,7-trichloro-1,3-tropolone exhibited high in vitro cytotoxic activity against A431 skin cancer and H1299 lung cancer cell lines.
Keywords: cytotoxic activity; fluorescence; o-chloranil; quantum chemical DFT calculations; 1,3-tropolones; X-ray diffraction